Analysis of the functional properties of porous friction layer (PFL) asphalt mixtures modified with ethylene vinyl acetate (EVA) waste (Revista Brasileira de Iniciação Científica, 2025)
The aim of the study was to evaluate the performance of CPA asphalt mixtures modified with EVA residue, in order to determine whether the material could improve the functional properties of asphalt mixtures. The methodology included a bibliographical study, collection of materials and laboratory tests on the samples produced by the study. The results showed that the CPA03 mix, with 3% EVA, had a tensile strength of 1.28 MPa, a void volume of 18.10% and a permeability coefficient of 0.18 cm/s, all within the normative parameters. In addition, the use of EVA reduced abrasive wear by 0.16% compared to the reference mix. It can be concluded that EVA improves the performance of mixtures, promotes sustainability and contributes to the circular economy.